Improving learning outcomes through modification of basketball games - Adityo Agustiawan; Novri Asri; M. Al Ghani (Sriwijaya Journal of Sport, 2022)
The research aims to improve the basketball game by modifying the game of SMP Negeri 40 Palembang students. The research method used is action research which consists of four steps: 1) planning, 2) implementation, 3) observation, and 4) reflection. The data collection is descriptive cumulative in the form of interviews and field notes. The research subjects were students of class VII, totaling 40 people. The results showed that student learning outcomes increased from 45.45% in the initial test data to 67.27 in the first cycle student learning outcomes increased from 63.63% to 80. Student improvement was reflected in the second cycle from 86.36% to 90. Based on the results of the study, it can be concluded that modifying the basketball game can improve student learning outcomes at SMP Negeri 40 Palembang.